2019
DOI: 10.1002/jcc.25857
|View full text |Cite
|
Sign up to set email alerts
|

KoBra: A rate constant method for prediction of the diffusion of sorbates inside nanoporous materials at different loadings

Abstract: We present a new method for calculating the diffusion tensor for the systems of sorbates inside nanoporous materials at different loadings by just using transition rate constants. In addition, a userfriendly program with graphical user interface has been developed and is freely provided to be used (https://sourceforge.net/projects/ kobra/). It needs from the user just to provide the values of the unit cell lengths and angles, the transition rate constants for each sorbate, and any spatial constraint between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…One of the most common in silico approaches for the risk assessment of NMs is the development of QSAR-type models, that quantitatively correlate the bioactivity and toxicity of NMs with descriptors encoding their structural characteristics. [170] For the classic QSAR approach, there are several methods for the calculation of theoretical-structural descriptors for GBMs including the valency-based topological indices of chemical networks proposed by Hayat et al (2018), [178] the distance-based topological descriptors presented by Arockiaraj et al (2019), [179] or other properties such as diffusion inside the GBM calculated by rates as proposed by Kolokathis et al (2019). [180] Based on the QSAR approaches, different ML approaches have been developed that make use, apart from the classic molecular descriptors, of other nano-related properties (e.g., physicochemical characterization data, quantum-mechanical descriptors, energy data calculated by MD simulations, omics data etc.)…”
Section: Qsar-type Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most common in silico approaches for the risk assessment of NMs is the development of QSAR-type models, that quantitatively correlate the bioactivity and toxicity of NMs with descriptors encoding their structural characteristics. [170] For the classic QSAR approach, there are several methods for the calculation of theoretical-structural descriptors for GBMs including the valency-based topological indices of chemical networks proposed by Hayat et al (2018), [178] the distance-based topological descriptors presented by Arockiaraj et al (2019), [179] or other properties such as diffusion inside the GBM calculated by rates as proposed by Kolokathis et al (2019). [180] Based on the QSAR approaches, different ML approaches have been developed that make use, apart from the classic molecular descriptors, of other nano-related properties (e.g., physicochemical characterization data, quantum-mechanical descriptors, energy data calculated by MD simulations, omics data etc.)…”
Section: Qsar-type Methodologiesmentioning
confidence: 99%
“…(2019), [ 179 ] or other properties such as diffusion inside the GBM calculated by rates as proposed by Kolokathis et al (2019). [ 180 ]…”
Section: Computational Approaches For Sbd Of Gbmsmentioning
confidence: 99%
“…TST methods can be used to estimate the diffusion coefficients in porous materials at slow diffusion time scales using the free-energy landscape . Such methods have been used for the estimation of diffusion coefficients of aromatics in MFI-type zeolites. ,, Caro-Ortiz et al showed that force fields for framework flexibility produce a zeolite structure that vibrates around a new equilibrium configuration with limited capacity to accommodate bulky guest molecules. To the best of our knowledge, molecular simulation studies where the effect of framework flexibility on the adsorption and diffusion of aromatics in zeolites is systematically studied are not available.…”
Section: Introductionmentioning
confidence: 99%
“…This allows for the simultaneous, exact treatment of spatial correlations on the surface that may be caused by adsorbate confinement or slow diffusion, [26,27] island formation, [28][29][30] lateral interactions, [1,14,18,19,[31][32][33][34][35] or substrate heterogeneity. [30,36,37] The numerical solution of the CME by KMC can be quite costly and, for some problems, there may be alternative approaches, [2,[38][39][40] such as solving the CME in Fourier space [41] or the tensor-train approximation. [42] In the limit of fast diffusion, the lattice structure becomes irrelevant, which simplifies the problem considerably.…”
Section: Introductionmentioning
confidence: 99%